Efficient numerical methods for aeroelastic analysis of wing-propeller configuration compound helicopters - Wang, Zi; Anobile, Alessandro; Popov, Atanas A. (2017)
Efficient numerical methods for time-domain aeroelastic analysis of a wing structure under a propeller-wing configuration is described in the paper. A linear beam model with deformable elastic axis under torsion and flapping is considered to simulate a wing structure with a tipmounted propeller, relying on efficient, analytical formulations. The complete aeroelastic system of equations is then solved using Galerkin’s approach, and numerically integrated by the Newmark-beta method. The computational tool developed is able to efficiently predict in the time domain the wing aeroelastic transient behaviour and the wing-propeller interaction effects. The purpose of the tool developed is to provide accurate enough predictions of the system aeroelastic response to be included in structural optimisation and control synthesis procedures. A detailed analysis on the solver used and an aeroelastic case study of a Eurocopter X3-like compound helicopter wing/propeller configuration are demonstrated.